Publisher Correction to: An exploration of subjective age, actual age, age awareness, and engagement in everyday. - Montepare, Joann M. (European Journal of Ageing, 2020)
Considerable research has documented relationships between subjective age and consequential outcomes such as life satisfaction, daily stress, health, and even mortality. Less is known about associations between the age people perceive themselves to be and everyday behaviors that may serve as the paths to broader life outcomes. To begin to fill this gap, this study explored the frequency with which 196 US adults aged 55–87 years engaged in behaviors reflecting nine behavioral domains. Respondents also answered questions about their subjective age, age awareness, and actual age. Results showed that whereas actual age predicted engagement in some behaviors (e.g., retirement activities), subjective age predicted engagement in most others (e.g., personal, social, grooming, body-focused, trend activities), and age awareness predicted participation in yet others (e.g., medical activities). The present findings provide insights both about age-related everyday behaviors, and the ways that several perceptions of age are differentially linked to their occurrence.